2023
DOI: 10.1038/s41467-023-38384-x
|View full text |Cite
|
Sign up to set email alerts
|

Solvent control of water O−H bonds for highly reversible zinc ion batteries

Abstract: Aqueous Zn-ion batteries have attracted increasing research interest; however, the development of these batteries has been hindered by several challenges, including dendrite growth, Zn corrosion, cathode material degradation, limited temperature adaptability and electrochemical stability window, which are associated with water activity and the solvation structure of electrolytes. Here we report that water activity is suppressed by increasing the electron density of the water protons through interactions with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(44 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…In general, the less active a free water is, the fewer H bonds it has. [ 17,18,23,24 ] However, it is observed that when salt concentration increases, the number of H‐bonds in each water molecule falls, ruling out this explanation as well. Therefore, it appears that mysteries remain over the origin of HER suppression in conventional salt aqueous electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the less active a free water is, the fewer H bonds it has. [ 17,18,23,24 ] However, it is observed that when salt concentration increases, the number of H‐bonds in each water molecule falls, ruling out this explanation as well. Therefore, it appears that mysteries remain over the origin of HER suppression in conventional salt aqueous electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the desolvation of the Zn 2+ solvation structure, the discharging process generates more free-MSM and free-water molecules on the Zn anode surface. It is reasonably considered that the hydrogen bonding between MSM and water molecules can partially limit the rapid decomposition of water , and benefit the formation of effective SEI on the Zn electrode/electrolyte interface, ,, as well as the Na + can suppress the Zn dendrite deposition, which are all beneficial to the stability of Na–Zn hybrid batteries.…”
Section: Results and Discussionmentioning
confidence: 99%
“…35 Meanwhile, splendid interfacial compatibility between the electrode and hydrogel electrolyte is the precondition for maintaining long-term stable cycling performance. 36–38…”
Section: Introductionmentioning
confidence: 99%